Building effective hedging strategies through financial variable analysis - Mukromiin, Ramadhan Khoerul; Purwidianti, Wida; Rachmawati, Erny; Yustina Rahmawati, Ika (Jurnal Mantik, 2025)
As international trade increases, so too does the risk involved. Therefore, good risk management is necessary to minimize the risks that arise. One way to do this is through hedging. This study aims to examine the impact of leverage, growth opportunity, firm size, profitability, and liquidity on hedging decisions in processing industry companies, which include two sectors: consumer cyclical and non-cyclical. The sample of this study was 30 companies listed on the IDX (idx.co.id) for the period 2020-2024. This study utilizes panel data comprising 150 observations, employing the binary logit estimation method, where the dependent variable is a dummy variable. This study provides an empirical contribution that reveals the relationship between financial factors (leverage, growth opportunity, firm size, liquidity, and profitability) on hedging decisions. The findings provide evidence that firm size and liquidity are dominant predictors of hedging decisions, with negative results, while other factors such as leverage, growth opportunity, and profitability do not affect hedging decisions, so that the results of this study can provide a new picture for companies in designing a more measurable hedging strategy and with this companies should focus more on managing their firm size and liquidity.